Reduce Waiting Times in the Multiple Server queuing model (M, M, C) (FCFS, âˆž, âˆž) "Model Proposal" - Hammadi, Abdulmunem. K.; Jaber, Samer Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The research aims to propose a plan to reduce the waiting times in the Multiple Server queuing model (M, M, C) (FCFS, âˆž, âˆž), and adopt this plan, mainly on the arrival rate (Î»), some process have been achieved in order to reduce the arrival rate per service channel that should  reduces the overall waiting time in the system.  This research is on two sections where the first deals with theory and how it has been approved the proposed method in theory and in mathematical equations as well as the second section, which dealt with the practical goal of applying the proposed method and comparing it with the traditional way, which was followed in calculating the performance measures in this model.